2023
DOI: 10.1002/berj.3860
|View full text |Cite
|
Sign up to set email alerts
|

Do they know what they know? Accuracy in teacher candidates' self‐assessments and its influencing factors

Abstract: Although self‐assessing one's knowledge is an integral part of a teacher's professional development, little is known about the accuracy of teacher candidates' self‐assessments. In particular, not much attention has been paid to their self‐assessment accuracy assessed on an individual level. Using measures from research on metacognition, we investigated the accuracy and bias of 513 mathematics teacher candidates who were tested in and self‐assessed their professional knowledge in the three core domains of mathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…Some documents are disqualified due to various reasons, such as irrelevant topics including STEAM education (Gregg-Jolly et al, 2016;Griese et al, 2015), chemistry (Promentilla et al, 2016), physics (Phang, 2010), photography (Cappello & Lafferty, 2015), general metacognition instead of mathematics education (Moulin & Souchay, 2015;Roll et al, 2007;Wall, 2008), or review articles on non-metacognition topics (Baumanns & Rott, 2021). Some documents discussing the concepts of elf-regulatory and self-efficacy in learning without directly mentioning metacognition were secured for processing, such as Ernst et al (2023) and Jain and Dowson (2009). Some studies were restored after the research group discussion, such as the research on metacognition in multiple subjects, including mathematics by Guo (2020).…”
Section: Step 3 Eligibilitymentioning
confidence: 99%
“…Some documents are disqualified due to various reasons, such as irrelevant topics including STEAM education (Gregg-Jolly et al, 2016;Griese et al, 2015), chemistry (Promentilla et al, 2016), physics (Phang, 2010), photography (Cappello & Lafferty, 2015), general metacognition instead of mathematics education (Moulin & Souchay, 2015;Roll et al, 2007;Wall, 2008), or review articles on non-metacognition topics (Baumanns & Rott, 2021). Some documents discussing the concepts of elf-regulatory and self-efficacy in learning without directly mentioning metacognition were secured for processing, such as Ernst et al (2023) and Jain and Dowson (2009). Some studies were restored after the research group discussion, such as the research on metacognition in multiple subjects, including mathematics by Guo (2020).…”
Section: Step 3 Eligibilitymentioning
confidence: 99%
“…To appropriately serve its function, students' self-assessments need to be accurate (Ernst et al, 2023). Regarding RQ2, numerous students often exhibit a tendency to inaccurately evaluate their own abilities (Max et al, 2022).…”
Section: Challenges Of Self-assessmentmentioning
confidence: 99%
“…Regarding RQ2, numerous students often exhibit a tendency to inaccurately evaluate their own abilities (Max et al, 2022). Ernst et al (2023) conducted a comprehensive literature review, revealing that students' relative accuracy remained notably low and exhibited a negative correlation with students' overconfidence. A parallel observation emerged from the study conducted by Chen and Zhang (2023), wherein participants who self-reported as 'highly accurate' in surveys predominantly achieved scores below the mean, while conversely, those who reported being 'not very accurate'…”
Section: Challenges Of Self-assessmentmentioning
confidence: 99%